Effects of soil management on soil parameters in nine German vineyards in summer 2017 - Martin Pingel; Annette Reineke; Ilona Leyer (PANGAEA, 2022)
Soil variables responding to different types of vineyard inter-row soil management were in the Rhein-Hesse area, Germany, in 2017. Each vineyard exhibited 4 experimental plots with four soil management types (complete cover, herbal seed mixture cover, alternating tillage, and complete tillage). In each vineyard, eight soil samples of the upper soil layer (0-10 cm) were taken, 2 neighboring inter-rows per plot. Soil sampling took place at the time of flowering of grapevines. Soil variables (soil organic carbon, total nitrogen, soil pH, and plant available nutrients (P, K, Mg), and bio-available copper) were measured using standard soil lab methods.
In: Pingel, M et al. (2022): Effects of soil management on vegetation parameters, soil parameters, soil microbial diversity and soil functions in nine vineyards in Rhine-Hesse, Germany, studied from 2016-2017 [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.948046